Analisis Strategi Pemasaran Digital pada Apotek Pendidikan Sekolah Farmasi ITB - Amir Amir; Muhammad Rayhan Savero (Syntax Corporation Indonesia, 2024)
This research aims to analyze and develop an effective digital marketing strategy for the Apotek Pendidikan Sekolah Farmasi ITB. This research uses IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) to identify internal and external factors, as well as appropriate marketing strategies for the company. In addition to qualitative descriptive analysis, this study also utilizes SWOT analysis (Strengths, Weaknesses, Opportunities, Threats), SWOT Cartesian Diagram, and SWOT Metrics as solutions obtained from the SWOT analysis. The results of this research show an IFAS score of 3.15 and an EFAS score of 2.65 indicating that the pharmacy has a very good ability to utilize existing external opportunities. In the Cartecius SWOT diagram, it is in a very advantageous position to grow rapidly (